Digital tools and critical thinking: enhancing information literacy competencies - Holovach, Tetiana (My University, 2025)
This study examines the integration of digital tools and critical thinking in enhancing information literacy competencies among students in contemporary educational environments. Through a comprehensive review of current research, the paper analyzes the relationship between technological proficiency and analytical reasoning skills in digital learning contexts. The research reveals that well-designed educational programs combining digital tool utilization with explicit critical thinking instruction produce significant improvements in students' ability to evaluate information, assess source credibility, and synthesize complex ideas from multiple sources. Key challenges identified include the digital divide, rapid technological change, and the proliferation of misinformation in digital environments. However, emerging opportunities through personalized learning systems, collaborative platforms, and innovative assessment methods demonstrate significant potential for advancing information literacy education. The findings suggest that successful implementation requires strategic pedagogical approaches, ongoing faculty development, and sustained institutional commitment to equity in access to digital resources. This research contributes to the growing body of literature on digital literacy education and provides practical recommendations for educational institutions seeking to enhance student critical thinking capabilities in the digital age. У цьому дослідженні розглядається інтеграція цифрових інструментів та критичного мислення у підвищення інформаційної грамотності студентів у сучасних освітніх середовищах. На основі всебічного огляду сучасних досліджень у статті аналізується взаємозв'язок між технологічною компетентністю та аналітичними навичками мислення в контексті цифрового навчання. Дослідження показує, що добре розроблені освітні програми, які поєднують використання цифрових інструментів з явним навчанням критичного мислення, значно покращують здатність студентів оцінювати інформацію, перевіряти достовірність джерел та синтезувати складні ідеї з різних джерел. Серед основних викликів, що були виявлені, – цифровий розрив, швидкі технологічні зміни та поширення дезінформації в цифрових середовищах. Однак нові можливості, що з'являються завдяки персоналізованим системам навчання, платформам для співпраці та інноваційним методам оцінювання, демонструють значний потенціал для розвитку освіти в галузі інформаційної грамотності. Результати дослідження свідчать, що для успішної реалізації необхідні стратегічні педагогічні підходи, постійний розвиток викладацького складу та стійка інституційна прихильність до рівності у доступі до цифрових ресурсів. Це дослідження є внеском у зростаючу літературу з питань освіти в галузі цифрової грамотності та надає практичні рекомендації освітнім закладам, які прагнуть покращити навички критичного мислення студентів у цифрову епоху.
Keywords: 2025а